Building a Strong Constitutional Court as Ideal State Institution - Prasetyo, Dossy Iskandar (Law Development Journal, 2024)
This article discusses the Strengthening of the Constitutional Court, in the sense of what strengthening needs to be done to strengthen the Constitutional Court in carrying out its constitutional duties. The duties in question include: guardian and interpreter of the constitution, protector of human rights, protector of citizens' constitutional rights, and protector of constitutional democracy. The ideal Constitutional Court must have all the requirements needed to carry out all of these duties relatively perfectly. It must be fit in various aspects: substance, structure, and culture. The study of the problem was conducted using the flow and working methods of doctrinal legal research of the theoretical research type, namely: research which fosters a more complete understanding of the conceptual bases of legal principles and of the combined effect of a range of rules and procedures that touch on a particular area of activity. The results of the study found that there are 7 (seven) aspects that need strengthening: (1). Strengthening Lawyer Statesman, (2). Strengthening the pattern of judge recruitment, (3). Expanding Authority, (4). Strengthening Professionalism, (5). Strengthening Accountability, (6). Strengthening Burden of Proof, (7). Strengthening the Honeste Vivere Culture.